Effects of titanium dioxide nanoparticles on nutrient absorption and metabolism in rats: distinguishing the susceptibility of amino acids, metal elements, and glucose. Issue 10 (25th November 2020) - Gao, Yanjun; Ye, Yixuan; Wang, Jing; Zhang, Hao; Wu, Yao; Wang, Yihui; Yan, Lailai; Zhang, Yongliang; Duan, Shumin; Lv, Lizhi; Wang, Yun
Abstract: Food grade titanium dioxide (TiO2 ) containing nanofractions, is commonly applied to whiten and brighten food products, which put consumers under health risks of ingesting TiO2 nanoparticles (NPs). Although the oral toxicity of TiO2 -NPs has been evaluated in several studies, gaps in knowledge exist regarding interactions between NPs and food components. Therefore, this study aimed to estimate the influence of TiO2 -NPs on nutrient absorption and metabolism through an in situ intestinal loop experiment which conducted on adult Sprague Dawley (SD) rats after 30-d gastrointestinal exposure to TiO2 -NPs of two different sizes (N-TiO2 and M-TiO2 ). Results showed that exposure to TiO2 -NPs caused flat apical membranes with sparse and short microvilli and inflammatory infiltration in small intestine. Both particles were absorbed into small intestinal cells, but N-TiO2 with smaller size could more easily be transported through gut and raise the blood titanium (Ti) levels. Changes in serum levels of amino acid were also different after exposure to these two particles. After injecting mixed solution of nutrients into in situ intestinal loop, the N-TiO2 exposure groups displayed significant absorption inhibition of the added histidine (His) and metabolism disorder of some non-added amino acid. However, no influence was observed on metal elements or glucose levels. This study identified TiO2 -NPs with small sizes could affect nutrient absorption and metabolism by inducing intestinal epithelium injury, and amino acids were more susceptible than metal elements and glucose. These findings suggested that foods supplemented with TiO2 -NPs should be carefully consumed by people with high protein requirements, such as children, the elderly, and patients with high metabolic disease or intestinal inflammation.